Microfluidic assay for precise measurements of mouse, rat, and human neutrophil chemotaxis in whole‐blood droplets. Issue 1 (27th January 2016) - Jones, Caroline N.; Hoang, Anh N.; Martel, Joseph M.; Dimisko, Laurie; Mikkola, Amy; Inoue, Yoshitaka; Kuriyama, Naohide; Yamada, Marina; Hamza, Bashar; Kaneki, Masao; Warren, H. Shaw; Brown, Diane E.; et al.
Abstract : A microfluidic assay enables precise characterization of neutrophil migration in the native blood environment, independent of the donor species, and at single cell resolution. Abstract : Animal models of human disease differ in innate immune responses to stress, pathogens, or injury. Precise neutrophil phenotype measurements could facilitate interspecies comparisons. However, such phenotype comparisons could not be performed accurately with the use of current assays, as they require the separation of neutrophils from blood using species‐specific protocols, and they introduce distinct artifacts. Here, we report a microfluidic technology that enables robust characterization of neutrophil migratory phenotypes in a manner independent of the donor species and performed directly in a droplet of whole blood. The assay relies on the particular ability of neutrophils to deform actively during chemotaxis through microscale channels that block the advance of other blood cells. Neutrophil migration is measured directly in blood, in the presence of other blood cells and serum factors. Our measurements reveal important differences among migration counts, velocity, and directionality among neutrophils from 2 common mouse strains, rats, and humans.